Stable Fly (Dog Fly) Control - Phillip E. Kaufman; Emma N. I. Weeks (EDIS)
The stable fly is a blood-sucking filth fly of considerable importance to people, pets, livestock, and the tourist industry in Florida. Filth flies, including stable flies, exploit habitats and food sources created by human activities, such as farming. Stable flies primarily attack animals for a blood meal, but in the absence of an animal host, they will bite people. This revised 4-page fact sheet was written by P. E. Kaufman and E. N. I. Weeks, and published by the UF Department of Entomology and Nematology, August 2012.